The Effects of Fiscal Policy on Inequality and Poverty in The Gambia - Carrasco Nunez, Haydeeliz; Jawara, Hamidou; Meyer, Moritz (World Bank, Washington, DC, 2022)
The overall objective of this study is to assess the impact of the fiscal system on poverty and inequality in The Gambia as of 2015. The study presents the first empirical evidence on the distributional impacts of taxes and social spending on households in The Gambia. Furthermore, it also evaluated the distributional effects of recent fiscal policy reforms in The Gambia. The assessment was based on the Commitment to Equity (CEQ) Methodology with data from the Integrated Household Survey of 2015 and fiscal administrative data from various government ministries, departments, and agencies. The analyses show that while the fiscal system in The Gambia reduces inequality by 1.2 Gini points, it increases the national poverty headcount by 5.3 percentage points as all households (including the poor) are net payers into the fiscal system. Most of the inequality reduction is due to primary education benefits, with a marginal contribution of 0.44 Gini points, and most of the poverty increase is due to custom duties and VAT with marginal contributions of -2.63 percentage points and -2.07 percentage points, respectively. Simulating the effect of changes in the structure of personal income tax (PIT) and the government’s ongoing absorption of the School Feeding Program indicate that these changes reduce inequality but do not offset the impoverishing effect of the fiscal system. Hence, more cashable transfer programs targeted to the poor are needed to offset the impoverishing effect of indirect taxes and make the fiscal system more pro-poor.